2013
DOI: 10.1016/j.ajhg.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Gene Encoding IFT Dynein Complex Component WDR34 Cause Jeune Asphyxiating Thoracic Dystrophy

Abstract: Bidirectional (anterograde and retrograde) motor-based intraflagellar transport (IFT) governs cargo transport and delivery processes that are essential for primary cilia growth and maintenance and for hedgehog signaling functions. The IFT dynein-2 motor complex that regulates ciliary retrograde protein transport contains a heavy chain dynein ATPase/motor subunit, DYNC2H1, along with other less well functionally defined subunits. Deficiency of IFT proteins, including DYNC2H1, underlies a spectrum of skeletal ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
115
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 48 publications
2
115
0
2
Order By: Relevance
“…78,79 A general role for hedgehog signalling in osteoblasts is suggested by conditions caused by mutations in genes whose protein products are required for ciliary func tion. Patients with Jeune asphyxiating thoracic dys tro phy, which is caused by a mutation in IFT80 ( encoding intraflagellar transport protein 80 homologue, a protein that inhibits cilia function) 80 have decreased hedgehog signalling in bone as well as decreased bone density. 80 IFT80 deficiency inhibits osteoblast formation, 81 and in vitro studies show that overexpression of GLI2 can rescue this defect in osteoblast differentiation.…”
Section: Heterotopic Ossificationmentioning
confidence: 99%
See 1 more Smart Citation
“…78,79 A general role for hedgehog signalling in osteoblasts is suggested by conditions caused by mutations in genes whose protein products are required for ciliary func tion. Patients with Jeune asphyxiating thoracic dys tro phy, which is caused by a mutation in IFT80 ( encoding intraflagellar transport protein 80 homologue, a protein that inhibits cilia function) 80 have decreased hedgehog signalling in bone as well as decreased bone density. 80 IFT80 deficiency inhibits osteoblast formation, 81 and in vitro studies show that overexpression of GLI2 can rescue this defect in osteoblast differentiation.…”
Section: Heterotopic Ossificationmentioning
confidence: 99%
“…Patients with Jeune asphyxiating thoracic dys tro phy, which is caused by a mutation in IFT80 ( encoding intraflagellar transport protein 80 homologue, a protein that inhibits cilia function) 80 have decreased hedgehog signalling in bone as well as decreased bone density. 80 IFT80 deficiency inhibits osteoblast formation, 81 and in vitro studies show that overexpression of GLI2 can rescue this defect in osteoblast differentiation. 81 Exces sive activation of hedgehog signalling in mature osteoblasts can also cause severe reduction of bone mass.…”
Section: Heterotopic Ossificationmentioning
confidence: 99%
“…Recent work from several groups has shown that mutations in the human orthologs of FAP133 (WDR34) and FAP163 (WDR60) cause skeletal ciliopathies (Huber et al, 2013; McInerney-Leo et al, 2013; Schmidts et al, 2013a). Although these data are consistent with WDR34 and possibly WDR60 being key components of human dynein-2, biochemical data validating this are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] No encontramos, en nuestro grupo, pacientes con polidactilia, descrita en el 14%. 3 Ocho niños (6 varones) con diagnóstico de displasia torácica asfixiante.…”
Section: Edad (Años) Estatura (Cm)unclassified
“…La herencia es autosómica recesiva, con considerable variabilidad en su expresión y heterogeneidad genética. 1,[3][4][5][6][7][8] El diagnóstico se realiza según criterios clínicos y radiológicos. 9 Se caracteriza por baja estatura, miembros cortos, braquidactilia, polidactilia.…”
Section: Introductionunclassified